The relationship of serum galectin-3 levels with obesity and insulin resistance - Altun, Özgür; Dikker, Okan; Akarsu, Murat; Arman, Yücel; Aydın Yoldemir, Şengül; Kutlu, Orkide; Özkan Gümüşkaya, Perihan; Tükek, Tufan (Journal of Surgery and Medicine, 2019)
Aim: Galectin-3 affects inflammation, cell adhesion, proliferation, differentiation and angiogenesis. Upon examining the pathogenesis of obesity and functions of galectin-3, we thought that galectin-3 may play a significant role in obese patients. This study aims to evaluate the relationship between obesity, insulin resistance and galectin-3 levels. Methods: Eighty five patients aged between 18-50 years were included in this cross-sectional study. BMI>30 were considered obese, those between 25-30 and 18-25 were considered overweight and normal weight, respectively. Patients with HOMA-IR>2.5 were considered insulin-resistant, and those with <2.5 were evaluated as insulin non-resistant.Galectin-3 levels were measured by Enzyme-linked immunosorbent assay. Results: Serum galectin-3 levels were significantly higher in obese patients, but not statistically significantly different between those with and without insulin resistance. Galectin-3 levels were also significantly correlated with BMI and total cholesterol levels, but not correlated with HOMA-IR. Conclusion: In obesity, serum galectin-3 levels may increase to compensate for the inflammation. Our results make it difficult to establish a relationship between insulin resistance and galectin-3.